BURGER ALLEN EXERCISE AGAINST THE CIRCULATION OF THE LOWER EXTREMITIES IN DIABETIC ULCER PATIENTS - Afida, Anna Martiana; Negara, Candra Kusuma; Chrismilasari, Lucia Andi (Sean Institute, 2022)
One of the effects of diabetes brought on by poor venous and arterial blood circulation is diabetic foot injury (LKD). Buerger Allen exercise is one modality of therapy that uses active postural movements to enhance blood flow in the lower extremities venous and arterial blood vessels. The brachial index ankle (ABI) technique was used to evaluate improved foot circulation. This study sought to assess the impact of Buerger Allen exercise on LKD patients' lower circulatory extremities. A quasi-experiment with a pretest and post-test without a control strategy was used as the research design. 43 respondents made up the 43 samples for this study, which were collected using successive sampling methods. Using bivariate data analysis, Wilcoxon tests were utilized to compare values before and after the Buerger Allen exercise. The findings demonstrated a statistically significant relationship between the average ABI in LKD patients before and after 0.85 (P-value = 0.000). The Buerger Allen exercise intervention is performed twice daily for three weeks. Positional changes and gravitational force variations can assist in emptying and filling blood vessels. At the same time, contraction of the gastrocnemius muscle and the plantar muscles as a muscle pump activates the ship and prevents backflow. Regular exercise can widen collateral circulation channels, boosting the supply of oxygen to peripheral tissues and the distribution of nutrients. Exercise helps increase circulation, according to studies by Buerger Allen. Therefore it can be suggested in the future that nurses teach patients with lower extremity circulatory disorders in LKD patients.